2022
DOI: 10.2217/fmb-2021-0299
|View full text |Cite
|
Sign up to set email alerts
|

G6PD Deficiency: Imbalance Of Functional Dichotomy Contributing to the Severity of COVID-19

Abstract: Human COVID-19 has affected more than 491 million people worldwide. It has caused over 6.1 million deaths and has especially perpetrated a high number of casualties among the elderly and those with comorbid illnesses. COVID-19 triggers a pro-oxidant response, leading to the production of reactive oxygen species (ROS) as a common innate defense mechanism. However, ROS are regulated by a key enzyme called G6PD via the production of reduced nicotinamide adenine dinucleotide phosphate (NADPH), which controls the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Studies have demonstrated that individuals with ADHD exhibited higher rates of infections including COVID-19 [25,26] with higher rates of severity [29,47] and complications [27]. Similarly, it was shown that G6PD-deficient individuals have a higher incidence of infectious diseases, indicating a predisposition to infections [40,41,45,46,48]. Our previous study showed that G6PD-deficient individuals had a higher risk of COVID-19 infection, of COVID-19 hospitalization, and of developing long-COVID [46].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies have demonstrated that individuals with ADHD exhibited higher rates of infections including COVID-19 [25,26] with higher rates of severity [29,47] and complications [27]. Similarly, it was shown that G6PD-deficient individuals have a higher incidence of infectious diseases, indicating a predisposition to infections [40,41,45,46,48]. Our previous study showed that G6PD-deficient individuals had a higher risk of COVID-19 infection, of COVID-19 hospitalization, and of developing long-COVID [46].…”
Section: Discussionmentioning
confidence: 94%
“…The dysregulation of reactive oxygen species (ROS) represents a crucial mechanism that can contribute to a heightened and more severe inflammatory response in individuals, thereby increasing the symptomatic nature of infection diseases [39,45,46]. Studies have demonstrated that individuals with ADHD exhibited higher rates of infections including COVID-19 [25,26] with higher rates of severity [29,47] and complications [27].…”
Section: Discussionmentioning
confidence: 99%
“…Our study only focused on the ubiquitination of MAVS and the TRAF family of the MAVS signalosome. (iii) Patients with deficiencies in the G6PD or GFPT2 were susceptible to recurrent infections and sepsis 33 , 34 . It remains unknown whether using a series of pharmacological, enhancing G6PD or GFPT2 activity would enhance antiviral response in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that G6PD-deficient individuals may be more predisposed to specific autoimmune diseases (Dore et al, 2023;Saha et al, 1982), infections (Abu-Osba et al, 1989;Mondal et al, 2022;Rostami-Far et al, 2016) and diabetes mellitus (Lai et al, 2017;Saha, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that G6PD-deficient individuals may be more predisposed to specific autoimmune diseases (Dore et al, 2023; Saha et al, 1982), infections (Abu-Osba et al, 1989; Mondal et al, 2022; Rostami-Far et al, 2016) and diabetes mellitus (Lai et al, 2017; Saha, 1979). Associations were found between G6PD deficiency and cardiovascular risk (Cocco et al, 1998; Dore et al, 2021; Meloni et al, 2008; Pes et al, 2019) in conflicting directions.…”
Section: Introductionmentioning
confidence: 99%